Systemic effects of Leucaena leucocephala ingestion on ringtailed lemurs (Lemur catta) at Berenty Reserve, Madagascar. Issue 6 (21st March 2015) - Crawford, Graham; Puschner, Birgit; Affolter, Verena; Stalis, Ilse; Davidson, Autumn; Baker, Tomas; Tahara, John; Jolly, Alison; Ostapak, Susan
<x xml:space="preserve">Abstract</x> Leucaena (Leucaena leucocephala) is a leguminous tree that is nutritious forage for domestic livestock when ingested in limited amounts. Unfortunately, leucaena contains mimosine, a plant amino acid, that can be toxic when ingested at higher concentrations. Reported toxic effects include alopecia (fur loss), poor body condition, infertility, low birth weight, thyroid gland dysfunction, and organ toxicity. Originally native to Mexico and Central America, leucaena has been introduced throughout the tropics, including Berenty Reserve, Madagascar where it was planted as supplemental browse for livestock. In Berenty, a seasonal syndrome of alopecia in ringtailed lemurs (Lemur catta) is associated with eating leucaena. Although much is known about the toxic effects of leucaena and mimosine on domestic animals and humans, the systemic effects on wildlife had not been studied. In a comparison of lemurs that include leucaena in their diet and those that do not, we found that animals that ingest leucaena absorb mimosine but that ingestion does not affect body condition, cause kidney or liver toxicity, or affect the intestinal tract. Alopecia is due to mimosine's interference of the hair follicle cycle. Leucaena ingestion is associated with higher serum albumin, α‐tocopherol, and thyroxine concentrations, suggesting that leucaena may provide some nutritional benefit and that lemurs can detoxify and convert mimosine to a thyroid stimulating metabolite. The primary conservation consequence of leucaena ingestion at Berenty may be increased infant mortality due to the infants' inability cling to their alopecic mothers. The widespread introduction of leucaena throughout the tropics and its rapid spread in secondary forest conditions mean that many other leaf‐eating mammals may be including this tree in their diet. Thus, exposure to leucaena should be considered when wildlife health is being evaluated, and the potential effects on wildlife health should be considered when contemplating leucaena introduction into or near wildlife habitat. Am. J. Primatol. 77:633–641, 2015. © 2015 Wiley Periodicals, Inc.